Prevention of Central Line-Associated Bloodstream Infection via Quality Improvement (The International Journal for Scientific Research, 2023)
Introduction: The economic burden of CLABSIs is substantial, with each infection estimated to add between $45,000 to $55,000 to hospital costs. The aim of this systematic review was to synthesize the current evidence on the prevention of CLABSI through quality improvement initiatives. Methods: A literature search was conducted using the following electronic databases: PubMed, MEDLINE, CINAHL, Cochrane Library, and EMBASE. The search was limited to studies published in the last 15 years, to ensure the relevance and timeliness of the data. The inclusion criteria were strictly defined to select high-quality interventional studies. Included studies were those that focused on interventions for the prevention of CLABSI and were conducted in hospital settings. Studies were excluded if they were non-interventional (such as reviews, editorials, and opinion pieces), focused on populations outside of hospital settings, or did not provide clear outcome measures related to CLABSI rates.  Results: A number of 8 studies were included with a common theme among the interventions was the implementation of comprehensive care bundles, which included components like staff education, hand hygiene protocols, and standardized catheter maintenance procedures. Comprehensive care bundles were particularly effective, with risk ratios (RRs) as low as 0.20 and 0.21, highlighting a reduction in infection rates by approximately 80%. Interventions involving antimicrobial catheters showed RRs ranging from 0.33 to 0.71, indicating a substantial decrease in CLABSI incidences. Moreover, staff training and education interventions resulted in RRs between 0.36 and 0.46, underscoring their importance in infection control.  Conclusions: The review revealed a broad range of sample sizes and methodologies, underscore the critical role of multifaceted, context-specific approaches in significantly reducing the incidence of CLABSIs and improving patient safety in hospital settings.
Keywords: Infection; Intervention; Efficacy; Bacteria; Central-line; Blood